1971
DOI: 10.3133/ofr71281
|View full text |Cite
|
Sign up to set email alerts
|

Al Kushaymiyah as a target for a Colorado-type molybdenite deposit

Abstract: Department of State, undertook a joint and cooperative effort to map and evaluate the mineral potential of central and western Saudi Arabia. The results of this program are being released in USGS open files in the United States and are also available in the Library of the Ministry of Petroleum and Mineral Resources. Also on open file in that office is a large amount of material, in the form of unpublished manuscripts, maps, field notes, drill logs, annotated aerial photographs, etc., that has resulted from oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…An earlier wadi-sediment survey detected anomalous amounts of tin and molybdenum in rocks from part of this unit (Theobald, 1970).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An earlier wadi-sediment survey detected anomalous amounts of tin and molybdenum in rocks from part of this unit (Theobald, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…One of these samples (170126) is within a 5-minute quadrangle area that was identified by Theobald (1970) as anomalous in tin and moybdenum, based on results of a regional wadi-sediment geochemistry survey.…”
Section: Plutonic Rocksmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies of other major tungsten anomalies in the Arabian Shield, for example, the quartz-vein stockwork systems at Al Kushaymiya (Whitlow, 1966;Theobald, 1971) and Baid al Jimalah (Cole and others, 1981), showed wolframite ((Fe, Mn) W04) as the principal tungsten mineral.…”
Section: Introductionmentioning
confidence: 99%
“…longitude be given a high priority. Theobald (1970) amassed and summarized values of tungsten, molybdenum, and tin determined on heavy mineral concentrates from wadi sediments collected from throughout much of the Arabian shield. In this report, Theobald postulated that the Kushaymiyah area, the general area Whitlow had previously recommended for further exploration, had close similarities with well-known areas of ore deposits in Colorado and New Mexico, U.S.A., and suggested that a study of the area should be undertaken in search of a stockwork molybdenite deposit.…”
Section: Previous Studiesmentioning
confidence: 99%